The use of non-wood fibres in the manufacture of paper with special reference to South African grown sisal fibre - Robertson, P. E.(Pierre Etienne) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.